(untitled) (Academic Journal of Internal Affairs, 2017)
There is no branch of the criminal sciences, from procedural doctrines to forensics, in which the studies of Endre Bócz could be circumvented. And there is no area of the profession, from the advocacy to the judiciary, where his name would not be mentioned with respect.